Information Communication Technology as Instrumental Activities of Daily Living for Aging-in-Place in Chinese Older Adults With and Without Cognitive Impairment: The Validation Study of Advanced Instrumental Activities of Daily Living Scale - Lai, Frank Ho-yin; Tong, Angela Yuk-chung; Fung, Ada Wai-tung; Yu, Kathy Ka-ying; Wong, Sharon Sui-lam; Lai, Cynthia Yuen-yi; Man, David Wai-kwong (Frontiers in Neurology, 2022)
(Background) The capability in applying information communication technology (ICT) is crucial to older peoples’ functional independence of community living nowadays. The proper assessment of individuals’ capability of ICT application is the corner stone for the future development of telemedicine in our aging population. (Methods) With recruitment of 300 participants of different functional and social background in home-living, hostel-living and care-and-attention home living; and through assessing individuals’ ability in instrumental activities of daily living and cognitive assessments, this study aimed at capturing the content validity and construct validity of the Advanced Instrumental Activities of Daily Living (AIADL scale) and to assesses the ability of older peoples’ in applying ICT and how the functional and social background affects their independence in aging-in-place. Moreover, this study captures the content validity and construct validity of the Advanced Instrumental Activities of Daily Living (AIADL scale). (Results) The AIADL scale showed good test-retest reliability and good-to-excellent internal consistency. In determining if the AIADL scale’s items measure various aspects of community living, exploratory factor analysis revealed a two-factor structure with “home living and management” and “community living”. Validity analysis with the known-groups method showed a high overall accuracy of prediction of individuals’ capability of independent living in the community. (Conclusions) The AIADL scale is a valid and reliable instrument to assess older adults’ ability in handling ICT as part of their instrumental activities in daily living. The scale can reflect older peoples’ capability in applying ICT. This instrument can serve as a reference in measuring individuals’ readiness in receiving tele-medicine and their ability of aging-in-place.